Emergência penal e garantias do Estado Constitucional de Direito: estudo sobre uma insuperável contradicão à luz do ordenamento jurídico brasileiro - Rafael Barros Bernardes da Silveira (2017)
The present work intends to demonstrate the incompatibility between the conceptions of criminal policy that legitimize the criminal intervention from the idea of emergency and the criminal law constructed based on the postulates of the Constitutional State of Law, consecrated in the Federal Constitution of 1988. In order to do so, it begins by exposing the characteristics of the State model proposed by Ferrajoli, especially by specifying the axioms that must be observed by criminal law and criminal procedural law. Then, the presence of these same principles will also be verified in the Brazilian constitutional text, either expressly or implicitly. In the sequence, we study the meaning of the term emergence in the lexicon and in areas of knowledge in general, only to later investigate the meaning attributed to it in the legal field, and more particularly in criminal law. It also refers to the notion of 'emergency criminal law' which has emerged in Italy to refer to a set of legislative measures and case-law decisions drawn up with a view to combating organized crime. Particular attention is also paid to the study of important criminal policy guidelines to analyze the extent to which the emergency is used to justify the criminal sanction. Finally, due to the prominence that the so-called "economic criminal law" has assumed today, there is a discussion on the use of "emergency" in the field of economic crime in order to justify the relaxation of traditional criminal guarantees.